(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Adenomyosis is a common pathological finding seen in reproductive age group women and also related to the menstrual charecteristics of the women. It is characterized by presence of endometrial tissue with or without hypertrophy of the surrounding myometrium. The preoperative diagnosis is based on clinical finding is very difficult. The aim of this study to determine the prevalence of adenomyosis in hysterectomy specimens done for benign gynecological condition and to find out the clinical profile associated with adenomyosis. Materials and methods: A prospective study done in women who were admitted for hysterectomy for benign gynecological conditions over a period of one year in the department of obstetrics and gynecology, Meenakshi medical college hospital and research institute. Adenomyosis was diagnosed based on histological report. The overall prevalence of adenomyosis, prevalence in different age group, and associated clinical features was studied. Results: In this study , 280 patients with benign gynecological condition was taken up for hysterectomy and among them 47 patients was diagnosed to have adenomyosis with a prevalence rate of 16.8%. The most common age group with adenomyosis is 41 to 50 years. It is also very common among multiparous women. The most common presenting symptoms is heavy menstrual bleeding followed by heavy menstrual bleeding with dysmenorrhea. Patients with prior history of dilatation and curettage also have strong association with adenomyosis. Conclusion: The prevalence of adenomyosis in hysterectomy specimen is 16.8% .The occurrence of adenomyosis is common in the age group of 31 to 40 years ,most common symptom being heavy menstrual bleeding and dysmenorrhea, prevalence increases with increased parity and with history of prior dilatation and curettage.Adenomyosis is a common cause for failed conservative management culminating in hysterectomy, posing risk to health related quality of women’s life. Hence the clinical diagnosis of adenomyosis should be considered in women presenting with these symptoms without any definitive evidence of uterine myomas, ovarian mass or uterovaginal prolapse.